“Making Slow Path”. The Arts-Based Event “Gebermte” as an Act of Commoning - Saavedra Bruno, Sofia; Isan, Lavinia; Balcha, Wossen Gebreyohannes; Van den Broeck, Pieter (Frontiers in Sustainable Cities, 2022)
This paper explores the transformative potential of Commoning for establishing an urban governance arrangement of an inter-municipal slow path connection located on a former railway embankment—the “Berm” in Mortsel, in the Province of Antwerp, Belgium. To do so, this paper makes use of French pragmatist sociology, namely the “Théorie des Cités (TdC)”, and proposes what we term a “TdC plus” (TdC+), which enhances the TdC with insights from personal psychology, interpersonal interactions and socio-institutional dynamics; the TdC+ also incorporates features of the Landed Commons (Grand Principles of the Landed Commons) into the TdC's approach of common good and operationalises it from an Action research perspective. The paper focuses on the transformative potential of “Gebermte 2019”, an arts-based local initiative aiming to support the establishment of a slow path on the Berm. It illustrates how small scale actions, such as citizens' cultural activities (considered as embedded in processes involving multiple actors over an extended period of time), can be instrumental in empowering civil society groups and help overcome conflict and foster collaboration. It explores the role of supralocal urban governance arrangements in making local initiatives more effective.